Skills needed for effective & efficient information professionals / Nur Marisa Badrulsham and Siti Wadhihah Mohd Nazri - Badrulsham, Nur Marisa; Mohd Nazri, Siti Wadhihah (Faculty of Information Management, 2014)
Information Professional (IP) is responsible for the overall management, organization, preservation, retrieval and dissemination of information in a particular organization that they are working for with the utilization of technology as one of their main tools. The degree graduates of Information Management Faculty produces IPs which comprise of librarians, web designers, web developers, archivists, chief information officers, information system specialists, information brokers, records managers and more. The type of organization or workplace for IPs can either be in the government or private sector such as at libraries, resource centres, information centres, and intranet departments. The ever-changing world of technology have caused IP's roles to develop and have the need to acquire various sets of skills to accommodate and perform their task efficiently with the use of the latest technology.